Factors affecting user intention to use gaming companion service - Huo, Shaohua; Abas, Wan Anita Wan; Waheed, Moniza (Frontiers in Communication, 2026)
Game companion services have emerged as a new form of entertainment in China. As gaming companion is a new phenomenon, many companion platforms are facing problems such as fierce market competition, imperfect platform technology and unprofessional services. Practical challenges increase the time cost for users to select companion services and weakens the quality of services they enjoy. Therefore, in order to help the platform better understand users, this study aims to investigate the users of the gaming companion platform. To achieve this goal, the Stimulus-Organism-Response (SOR) theory was utilized in designing the quantitative survey questionnaire. A simple random sampling technique was employed, resulting in responses from 425 gaming companions in Shanghai, China. The collected data were then analyzed using structural equation modeling (AMOS 26.0). The results of the analysis showed that professionalism, interactivity, and popularity have a significant positive effect on user’s perceived value (perceived entertainment and perceived sociability). Meanwhile, the study found a mediating effect of perceived entertainment and perceived sociability. The characteristics of the accompanist (professionalism, interactivity and popularity) enhance the user’s intention to use through enhancing the perceived value. This study reveals the essence of user research in the field of mass communication, demonstrating that social interaction and entertainment experiences are the core drivers influencing user behavior. This study provides a theoretical foundation for future user research in the field of game companion. This study provides help for gaming companion platforms to develop more effective operation strategies to promote the sustainable development of the gaming companion industry.